The bright side of digitization: Assessing the impact of mobile phone domestication on left-behind children in China's rural migrant families - Tang, Jiamei; Wang, Ke; Luo, Yuming (Frontiers in Psychology, 2022)
This study examines the usage of mobile phones and its impact on rural left-behind children (LBC) problem in China, when one or both the parents migrate to cities for better earnings. The study has used ethnographic approach by using participants’ observations and conducted interviews from 21 LBC, residing in Guangren village, south China’s Guangxi autonomous region. The study uses domestication theory to analyze the adoption of mobile phones and its impact on their daily routines and spaces in and out of their households. The key findings are: (a) the LBC used mobile phones primarily to engage with their distant parent(s); (b) through collaborative efforts, they tried to enhance familial connections; and (c) they overcame the separation issue by co-participating in ongoing events, thus, making the domestication of mobile phone a distant solving of real-world problems faced by migrant parent(s) and their LBCs. The study concludes that LBC’s innovative uses of mobile phone empowered them, by building shared virtual space with their migrant parent(s), to handle the separation issue. In such shared virtual spaces, LBC’s families have developed rich expressions of familial connections in various forms, based on limited perpetuate connectedness.